Individuals’ Power Persistence in Teams: A Study Examining the Effects of Individuals’ Competence, Uncooperative Behavior and Team Performance in the National Basketball Association - Mammassis, Constantinos S.; Schmid, Petra C. (Frontiers in Psychology, 2022)
This paper examined (a) the persistence of individuals’ power in teams and (b) the individual- and team- level factors influencing power maintenance and loss in the long-term (i.e., power dynamics). Specifically, and in line with the functional theory of power, we showed that individuals’ state of power in the past exerted a significant behavioral impact on their later state of power, hence, confirming the “power persistence” hypothesis. Furthermore, and in accordance with the conflict theory of power, we found that individuals’ competence positively influenced power above and beyond its persistence. We also showed that individuals’ uncooperative behavior and team performance had a negative and significant effect on individuals’ power above and beyond its persistence. Finally, we discussed the importance of individuals’ power dynamics for effectively managing power struggles in teams.